Lyrics in terracotta at Kantajeer Mandir - Sirajuddin, Muhammad (Dhaka : Markup International, 1992)
About the 18th century Hindu temple in ruin at Kantanagar, a place 21 km. north of Dinajpur Town, Bangladesh.
Includes bibliographical references (p. [88]).
Keywords: Kantanagar Temple; Hindu gods in art; Terra-cotta sculpture, Indic -- Bangladesh -- Kantanagar; Kantanagar (Bangladesh) -- Buildings, structures, etc